Horizontal hollow pipes used as vibration isolation barriers: Numerical modelling and design optimization. (November 2022) - Hu, Zhonghua; Chen, Qingsheng; Xu, Changjie; Basack, Sudip; Luo, Wenjun
Abstract: Open trenches are one of the most popular vibration isolation techniques used to reduce the transmission of ground vibrations. Despite several advantages of this systems for isolating ground vibrations, the major drawback is the geotechnical instability of the trenches. To solve this issue, the author have created a novel approach that involves filling the open trenches with hollow pipes in specific pattern. This is a novel method for mitigating ground vibrations by burying hollow pipes horizontally. Through the use of three-dimensional (3D) finite-element modeling, the effectiveness of such hollow pipes in decreasing ground vibrations generated by harmonic stress excitation on the ground surface was investigated. Compared to open trench barriers and in-filled trench, these pipe assemblages have been demonstrated to be highly successful in reducing ground vibration transmission while addressing issues of instability and enhancing vibration isolation efficiency. In PLAXIS 3D, a dynamic numerical model is developed, and the results are validated against available solutions. Then, an optimized design technique for wave barriers is developed, and explore the effect of layered soil on vibration isolation effectiveness of hollow pipes.